The Effect of Leadership, Work Culture, Work Environment, Interpersonal Communication, Workload on Nurse Loyalty in the Public Health Center - Wahyuningrat Wahyuningrat; Teddy Rusmawan (Journal of Industrial Engineering & Management Research, 2022)
The research objective was to determine the influence of leadership on loyalty, the influence of work culture on loyalty, the influence of the work environment on loyalty, the influence of interpersonal communication on loyalty, and the effect of workload on loyalty. This research method is a quantitative method with a survey through online questionnaires distributed through social media. The questionnaires were designed using a Likert scale of 1 to 7. Respondents to this study were 269 senior public health center employees who were determined by simple random sampling. Data analysis used the structural equation modeling (SEM) method with SmartPLS 3.0 software tools. The stages of data testing are validity, reliability, termination and hypothesis testing. The independent variables in this study are Leadership, Work Culture, Work Environment, Interpersonal Communication and Workload. The dependent cariabel in this research is Loyalty. The results of hypothesis testing show that leadership has a positive and significant effect on loyalty, work culture has a positive and significant effect on loyalty, work environment has a positive and significant effect on loyalty, interpersonal communication has a positive and significant effect on loyalty, workload has a positive and significant effect on loyalty.